I can provide the proof for A. tax multiplier = -mpc / (1 - mpc):
The tax multiplier is the change in real GDP divided by the change in taxes. It can be represented by the formula:
Tax multiplier = ΔY / ΔT
Given the consumption function equation: C = a + (mpc * (Y-T)), where:
- C is consumption
- a is autonomous consumption
- mpc is the marginal propensity to consume
- Y is real GDP
- T is taxes
If we take the derivative of the consumption function with respect to Y, we get the marginal propensity to consume:
dC/dY = mpc
Now, let's differentiate the consumption function with respect to taxes T:
dC/dT = -mpc
Therefore, the change in consumption with respect to a change in taxes (ΔT) will be:
dC = -mpc * ΔT
Substitute this back into the tax multiplier formula:
Tax multiplier = ΔY / ΔT
ΔY / ΔT = -mpc * ΔT / ΔT
ΔY / ΔT = -mpc
Therefore, the tax multiplier is equal to -mpc / (1 - mpc).
I hope this helps with the understanding of the tax multiplier formula. Let me know if you would like me to explain the government multiplier formula as well.
1. Proof that
A. tax multiplier= -mpc/1-mpc
B. government multiplier = 1/1-mpc
1 answer